Arrhythmic event prediction in patients with heart failure and reduced ejection fraction. Issue 2 (February 2021) - Santangelo, Gloria; Bursi, Francesca; Negroni, Maria S.; Gentile, Domitilla; Provenzale, Giovanni; Turriziani, Laura; Zambelli, Daniel L.; Fiorista, Lorenzo; Bacchioni, Giuseppe; Massironi, Laura; Tarricone, Diego G.; Carugo, Stefano
Abstract : Aims: Implantable cardioverter defibrillator (ICD) is an effective treatment to reduce mortality in patients with symptomatic heart failure and left ventricular ejection fraction (LVEF) 35% or less. LVEF presents a low sensitivity for predicting arrhythmic events. Aim of this study was to identify predictors of sustained ventricular arrhythmias (SVAs), overall and according to the cause of heart failure. Methods: Single-center, retrospective, cohort study of 193 patients (51 nonischemic and 142 ischemic) with chronic heart failure and LVEF less than 35% who had received ICD for primary prevention of sudden cardiac death. We collected clinical data, echocardiographic parameters and SVAs detected by the ICD. Results: During a median follow-up of 1440 days, 32 (16.2%) patients had SVAs. SVAs incidence was similar in patients with nonischemic (15.6%) and ischemic cause of heart failure (16.9%). Hypertension, diabetes, chronic renal failure, atrial fibrillation, chronic obstructive pulmonary disease, New York Heart Association class at least III were predictors at univariate analysis of SVAs. A clinical score, assigning one point to each of these variables, was associated with a significantly increased risk of SVAs [odds ratio for each point increase = 1.92, 95% confidence interval 1.40–2.65, P < 0.0001, area under the curve (AUC) 0.73], with 72% sensitivity and 60% specificity for a cutoff at least three and remained significant in nonischemic (AUC 0.84) and ischemic (AUC 0.68) patients. Conclusion: Our study shows the benefit of ICD implantation in primary prevention and its independency of cause. A simple clinical score, based on comorbidities, identifies patients with more benefits from ICD implantation.